Propiedades y características reológicas aplicadas en el yogur - Mendoza Mendoza, Rosa Elena (2021)
Yogurt viscosity is an important aspect in quality and sensory acceptance by the consumer. It is important to understand the mechanisms involved in the processing and how these viscosity parameters improve the quality of the product. The aim of this review is to determine the main factors that influence the rheological characteristics during the processing of stirred yogurt. We reached our goal by of a systematic investigation of scientific articles using the PRISMA method for the inclusion and exclusion of information. The variables that intervene during the elaboration of yogurt in stages such as standardization, pasteurization, inoculation, stirring and storage that affect the viscosity of stirred yogurt were analyzed, establishing temperatures, times for each stage and unitary operation based on the information provided by previous research. The characteristics of the sample, the equipment used and cutting speed were analyzed in order of establish a standardized method in the protocols for the determination of the rheological characteristics and properties of stirred yogurt. The analysis enabled us to establish that the viscosity of yogurt is influenced especially by the physical-chemical characteristics of the milk and processes such as standardization, pasteurization, incubation and stirring during the preparation of yogurt. Viscosity analysis, variables such as viscometer type, spindle combination, rotor speed and sample conditions affect the accuracy of the reading and the actual viscosity value.